جهود الشيخ طاهر التليلي السوفي في النظم القرآني (مجلة الواحات للبحوث والدراسات, 2021)
The Scientists Of The Islamic Nation In General And Algeria In Particular Have A Significant Contributions To The Service Of The Islamic Sciences And Their Collection, In Many Ways And Methods, And Perhaps The Most Prominent Of Which Is The Establishment Of Scientific Systems With Multiple Images And Many Fields, And At The Forefront Of These Systems Is Related To The Quran "Kitab Allah" And The Statement Of Quran Science Such As Strange, Drawing And Control Issues And So On. And Sheikh Mohammed Al-Tahir Talili Among The Prominent Ones Who Had A Clear Contribution In This Area Through The Qurranic Systems That Went Out To Light And "And Thanks To Allah" Achieved, But It Is Still Immersed And Unknown To Students, Researchers And Practitioners To Teach And Memorize The Quran. Accordingly, This Research Is A Double Task , Get To Know The Sheikh Talili, On The One Hand, And The Other Sheds Light On Those Quranic Systems That May Be Useful For Researchers To Take Advantage Of His Heritage In General, Which Is Still Too Much Scripted.In Order To Achieve This Goals, The Research Included Two Two Matters , The First Concerned The Definition Of The Shaykh, May Allah Have Mercy On Him, And The Second Is To Get To Know The Efforts Of The Shaykh In The Qur'anic Systems, And In Conclusion Reached The Most Important Results Obtained.   Keywords: Sheikh Mohammed Tahir Talili, Quranic Systems, Efforts.